Interannual variation of the Warm Arctic–Cold Eurasia pattern modulated by Ural blocking and the North Atlantic Oscillation under changing sea ice conditions - Zhou, Xiling; Sato, Tomonori; Li, Shixue (Progress in Earth and Planetary Science, 2023)
Together with rapid Arctic warming and sea ice decline, especially over the Barents–Kara seas (BKS), extreme cold winters have occurred frequently in mid-latitudes, particularly in Central Eurasia. A pattern with two distinct winter temperature anomalies centered over the BKS and Central Eurasia is known as the Warm Arctic–Cold Eurasia (WACE) pattern. The impacts of sea ice loss over the BKS and internal atmospheric variability on past WACE formation remain under discussion mainly due to the large internal atmospheric variability in the mid-latitudes. This study analyzed a large-ensemble historical experiment prescribing observed sea ice condition to investigate the role of internal atmospheric variability in the observed interannual variation of the WACE pattern. Comparison of ensemble members suggests that internal atmospheric variability is important for regulating the magnitude of the WACE pattern. Besides the strong effect of local sea ice loss, winter temperature over the BKS increases due to warm advection driven by the Ural blocking and positive phase of the North Atlantic Oscillation. A decrease in winter temperature over Central Eurasia is mainly attributable to the cold advection enhanced by Ural blocking rather than the remote effect of sea ice decline over the BKS. Our study reveals the importance of internal atmospheric variability in elucidating the observed interannual variation of the WACE pattern.